2020
DOI: 10.1111/jmi.12828
|View full text |Cite
|
Sign up to set email alerts
|

The lost portrait of Robert Hooke?

Abstract: Summary This letter considers the ‘Portrait of a Mathematician’ attributed to Mary Beale in the 1680s as a likely candidate for a portrait of Robert Hooke made during his lifetime. It closely matches the physical descriptions of Hooke made by his biographers who knew him, Richard Waller (d. 1715) and John Aubrey (1626–1697). The portrait contains a remarkable diagram, as well as its mechanical analogue, demonstrating the elliptical orbit of a body under constant force similar to an unpublished, unfinished 1685… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In his Letter regarding my Paper, Dr Whittaker suggests that the sitter in Mary Beale's ‘Portrait of a Mathematician’ is Isaac Barrow 1,2 . Indeed there is a portrait of Isaac Barrow by Mary Beale and it can be found in Trinity College, Cambridge, Figure 1.…”
Section: Figurementioning
confidence: 97%
“…In his Letter regarding my Paper, Dr Whittaker suggests that the sitter in Mary Beale's ‘Portrait of a Mathematician’ is Isaac Barrow 1,2 . Indeed there is a portrait of Isaac Barrow by Mary Beale and it can be found in Trinity College, Cambridge, Figure 1.…”
Section: Figurementioning
confidence: 97%
“…[11] Professor Lawrence Griffing's more recent claim that Mary Beale's Portrait of a Mathematician, c1680 (Figure One), depicts Robert Hooke is similarly unconvincing. [12] [13] Following a detailed examination of Hooke's contribution to microscopy he indicated that his attribution is based upon two major elements: that the diagram in the painting was from Hooke's 1685 unpublished paper The Laws of Circular Motion; and that the sitter resembles the contemporary descriptions of Hooke.…”
Section: Previous Attempts To Identify a Portrait As Robert Hookementioning
confidence: 99%
“…The pantheon of early histology pioneers. From left to right are: A painting entitled “Portrait of a Mathematician” attributed to Mary Beale that is believed to depict Robert Hooke 5 ; a painting of Marcello Malpighi by Carlo Cignani; a painting of Marie‐François Xavier Bichat by Pierre‐Maximilien Delafontaine; and an engraving of August Franz Josef Karl Mayer by Adolf Hohnek.…”
Section: Introductionmentioning
confidence: 99%